2022
DOI: 10.1021/acsnano.1c10708
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Counting of Multiplexed Nanoparticle Emitters in Single Cells and Organelles

Abstract: Nanomaterials are the subject of a range of biomedical, commercial, and environmental investigations involving measurements in living cells and tissues. Accurate quantification of nanomaterials, at the tissue, cell, and organelle levels, is often difficult, however, in part due to their inhomogeneity. Here, we propose a method that uses the distinct optical properties of a heterogeneous nanomaterial preparation in order to improve quantification at the single-cell and organelle level. We developed “hyperspectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Due to the optical diffraction limit of our system (∼500 nm) and the pixel size of our detector (∼150 nm), emission from a single SWCNT is blurred across a minimum of 3 × 3 pixels in NIR fluorescence images, and thus, small bundles and aggregates of SWCNTs could not be resolved from the single-nanotube population using Feret’s diameter measurements. Therefore, we employed a spectral counting method to investigate the degree of aggregation for each sample . Hyperspectral cubes of the spin-coated DNA–SWCNTs were acquired and again split into fluorescent ROIs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the optical diffraction limit of our system (∼500 nm) and the pixel size of our detector (∼150 nm), emission from a single SWCNT is blurred across a minimum of 3 × 3 pixels in NIR fluorescence images, and thus, small bundles and aggregates of SWCNTs could not be resolved from the single-nanotube population using Feret’s diameter measurements. Therefore, we employed a spectral counting method to investigate the degree of aggregation for each sample . Hyperspectral cubes of the spin-coated DNA–SWCNTs were acquired and again split into fluorescent ROIs.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we sought to investigate how the intracellular processing of DNA–SWCNTs can vary depending on the dispersion quality. As a quantitative measure of this processing, the endosomal loading of DNA–SWCNTs was interrogated using the same hyperspectral counting approach previously described within single intracellular ROIs of the three cell lines . Hyperspectral cubes were acquired at 100× magnification for each cell type following a 30 min pulse of 250k-SWCNTs or 1k-SWCNTs and an additional 30 min of incubation in fresh media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, accumulating evidence has suggested that mesoporous silica nanoparticles (MSNs) play a vital role in drug delivery systems due to their low toxicity, superior biocompatibility, a large pore volume and surface area, and simplicity of functionalization ( Chen et al, 2022 ; Wei et al, 2022 ). Thus, MSNs have been widely utilized to load DNA ( Lin-Shiao et al, 2022 ; Ma et al, 2022 ), drugs ( Song et al, 2022 ; Zhang et al, 2022 ) and light ( Semcheddine et al, 2021 ; Jena et al, 2022 ) for cancer therapy and diagnosis. Furthermore, in order to increase the targeting efficiency, nanoparticles modified with a DNA or RNA aptamer are considered to be more promising owing to their low immunogenicity, smaller size, and active targeted property.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Single-walled carbon nanotubes (SWCNTs), visualized as a 1D cylinder of a rolled-up sheet of carbon atoms arranged in a honeycomb lattice, find numerous biomedical applications, including imaging and sensing in the nIR. [10][11][12][13][14][15] With an inner diameter of 1-2 nm and length of 300 nm -10 μm, [16] SWCNTs have unique physical, chemical, mechanical, and electronic properties. In particular, SWCNTs emit bright fluorescence in the nIR range (900-1400 nm), which does not photobleach nor blink.…”
Section: Introductionmentioning
confidence: 99%